Porous refractory, manufacturing method thereof, and gas blowing plug

The porous refractory material, characterized by specific pore size distribution and composition, addresses the challenges of air permeability and molten steel penetration in gas blowing plugs, achieving enhanced ventilation and strength.

JP7648923B2Active Publication Date: 2025-03-19SHINAGAWA REFRACTORIES CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023045852
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2025-03-19
Estimated Expiration
2043-03-22

AI Technical Summary

Technical Problem

Existing porous refractory materials used in gas blowing plugs face challenges in achieving high air permeability while maintaining sufficient strength to prevent molten steel penetration, and they often have uneven porosity and insufficient ventilation rates due to the use of natural-derived raw materials.

Method used

A porous refractory material with an average pore diameter of 230 μm or less, a span value of 0.8 or less, and an air permeation rate of 1.2 × 10^-10 m² is achieved by using a specific composition of fire-resistant raw materials and acrylic resin, which is kneaded, molded, and fired to produce a refractory with uniform internal porosity and enhanced ventilation properties.

Benefits of technology

The resulting porous refractory exhibits excellent ventilation properties and is effective in suppressing the penetration of molten steel, while maintaining high strength and uniform porosity distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648923000001
    Figure 0007648923000001
  • Figure 0007648923000002
    Figure 0007648923000002
  • Figure 0007648923000003
    Figure 0007648923000003
Patent Text Reader

Abstract

To provide porous refractory having excellent gas permeability and easily preventing penetration of molten steel, and a method of producing the same.SOLUTION: The porous refractory has a mean pore diameter d50 of 230 μm or smaller which is a cumulative 50% pore diameter on the volume basis measured by the mercury porosimetry of JIS R1655, has a span value 'a' of the pore diameter expressed by formula (1) of 0.8 or below and has an air permeability measured by JIS R2115 of 1.2(×10-10 m2) or higher. Formula (1): a=(d10-d90) / d50, provided that d50 is a mean pore diameter, d10 and d90 are each a cumulative 10% pore diameter and a cumulative 90% pore diameter respectively on the volume basis from the large pore diameter side, measured by the mercury porosimetry of JIS R1655.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous refractory, a method for manufacturing a porous refractory, and a gas blowing plug. [Background technology]

[0002] In refining in a ladle, inert gas such as argon gas is blown into the molten steel and refining agents from a gas blowing plug attached to the bottom of the ladle to mix the molten steel and refining agents, with the aim of homogenizing the temperature and composition of the molten steel. Typical gas blowing plugs include those made of porous refractories, those made of dense refractories with through holes, and those made of dense refractories with slits. Gas blowing plugs made of porous refractories are widely used due to the ease of gas flow control and bubbling reliability.

[0003] In gas blowing plugs using porous refractories, high permeability is required to blow gas efficiently. In order to increase the permeability, it is possible to increase the porosity or pore size of the porous refractory. However, if the porosity is too high, the strength of the refractory may be weakened or it may become impossible to prevent the penetration of molten steel. Also, if the pore size is too large, it may become impossible to prevent the penetration of molten steel.

[0004] One method for increasing the air permeability while suppressing the increase in porosity and pore size is to add a burnt raw material during the manufacture of a refractory. When a molded body made by adding a burnt raw material to a refractory raw material is fired at high temperature, the refractory raw material remains while the burnt raw material is burned. It is believed that the burnt raw material burns down the closed pores inside the molded body to form interconnected pores, resulting in improved air permeability of the porous refractory after firing.

[0005] Patent Document 1 discloses an invention for producing a porous refractory material using wood chips as a burnt raw material, and Patent Document 2 discloses an invention for producing a porous refractory material using charcoal powder as a burnt raw material.

[0006] However, when wood chips are used as in Patent Document 1, the wood chips are crushed in the molding process, and the desired pores cannot be formed in the firing process, and as a result, the porous refractory may not have sufficient air permeability. In addition, if the maximum pressure of the press molding is lowered to prevent the burnt raw material from being crushed, the porosity of each part of the porous refractory may become uneven. Furthermore, when a burnt raw material that is naturally derived and whose components are difficult to control, such as the wood chips in Patent Document 1 or the charcoal powder in Patent Document 2, is used, there are cases where a burnt residue is generated and the porous refractory after firing may not have sufficient air permeability. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2014-043377 A [Patent Document 2] JP 2013-001584 A Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a porous refractory material which has good gas permeability and is easy to inhibit the penetration of molten steel, and a method for producing the same. [Means for solving the problem]

[0009] The porous refractory according to the present invention has an average pore diameter d50, which is the cumulative 50% pore diameter based on the volume of the pores, specified by the mercury intrusion method according to JIS R1655, of 230 μm or less, a pore diameter span value a represented by the formula (1) of 0.8 or less, and an air permeability specified by JIS R2115 of 1.2 (× 10 -10 m 2 )That's all. a = (d10-d90) / d50 (1) d50 is the average pore diameter, and d10 and d90 are the cumulative 10% pore diameter and cumulative 90% pore diameter, respectively, from the larger pore diameter side on a pore volume basis determined by mercury intrusion porosimetry according to JIS R1655.

[0010] According to this configuration, it is possible to provide a porous refractory material that has good air permeability and is easy to prevent the penetration of molten steel.

[0011] In one embodiment, the porosity specified by JIS R2205 is 40% or less.

[0012] According to this configuration, it is possible to provide a porous refractory material that is more likely to prevent penetration of molten steel and has high strength.

[0013] Further, the method for producing a porous refractory according to the present invention includes the steps of: A kneading step of kneading the refractory raw material with an acrylic resin in an amount of 3% by mass or more and 15% by mass or less relative to 100% by mass of the refractory raw material to obtain a kneaded mixture; A molding step of molding the kneaded mixture to obtain a molded body; and A firing step of firing the molded body to obtain a porous refractory material, The acrylic resin has an average particle diameter D50, which is the cumulative 50% diameter of a volume-based particle size distribution specified by a laser diffraction / scattering method according to JIS Z8825, of 30 μm or more and 70 μm or less, and a span value A of the particle diameter expressed by formula (2) is 3.5 or less. A = (D90-D10) / D50 (2) D50 is the average particle size, and D10 and D90 are the cumulative 10% diameter and cumulative 90% diameter, respectively, from the smaller particle diameter side of the volume-based particle size distribution specified by the laser diffraction / scattering method of JIS Z8825.

[0014] According to this configuration, a method for producing a porous refractory material that has good gas permeability and is easy to prevent penetration of molten steel can be provided.

[0015] In one embodiment, the molding process includes a press molding step, and a maximum pressure of the press molding step is 10 MPa or more.

[0016] According to this configuration, it is easy to manufacture a porous refractory material having a uniform internal porosity distribution.

[0017] In one embodiment, The refractory raw material contains 55% to 95% by weight of aggregate raw material having a particle size of 0.1 mm to 5.0 mm, and 5% to 45% by weight of fine powder raw material having a particle size of less than 0.1 mm.

[0018] According to this configuration, it is possible to provide a method for producing a porous refractory material that has better air permeability and is more likely to prevent penetration of molten steel.

[0021] The gas-blowing plug according to the present invention includes any one of the porous refractories described above.

[0022] According to this configuration, it is possible to provide a gas blowing plug which has good gas permeability and which easily prevents the penetration of molten steel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] A preferred embodiment of the present disclosure will be described in detail below. Note that the embodiment described below does not unduly limit the contents of the present disclosure described in the claims, and all of the configurations described in the embodiment are not necessarily essential as a means for solving the problems of the present disclosure.

[0024] [Configuration of porous refractory material] The porous refractory according to the present embodiment includes a refractory raw material and may include other components described below. The porous refractory according to the present embodiment has a predetermined gas permeability characteristic.

[0025] (Components of porous refractories) 1.Refractory raw materials The type of refractory raw material is not particularly limited and may be any known raw material. The refractory raw material may include aggregate raw material and fine powder raw material, and may also include glaze (frit) and binder. The blending ratio of these types of raw materials may be appropriately adjusted.

[0026] The aggregate raw material is the main component of the refractory raw material. The type of aggregate raw material is not particularly limited, and may be any known aggregate raw material such as various spherical alumina, crushed alumina, mullite, magnesia, etc. The particle diameter of the aggregate raw material is preferably 0.1 mm or more, more preferably 0.2 mm or more. When the particle diameter of the aggregate raw material is 0.1 mm or more, the pore diameter becomes large, which is preferable because it is easy to ensure air permeability. In addition, the particle diameter of the aggregate raw material is preferably 5.0 mm or less, more preferably 4.0 mm or less. When the particle diameter of the aggregate raw material is 5.0 mm or less, the pore diameter does not become too large, which is preferable because it is easy to ensure resistance to molten steel infiltration.

[0027] The content of the aggregate raw material in the entire refractory raw material is preferably 55% by mass or more, more preferably 60% by mass or more. When the content of the aggregate raw material is 55% by mass or more, it is preferable because it is easy to form uniform gas passages and ensure breathability. In addition, the content of the aggregate raw material in the entire refractory raw material is preferably 95% by mass or less, more preferably 92% by mass or less. When the content of the aggregate raw material is 95% by mass or less, it is preferable because it is easy to ensure interparticle bonding force.

[0028] The fine powder raw material can play a role in enhancing the bonding force between particles in the refractory raw material. The type of the fine powder raw material is not particularly limited, and may be any known fine powder raw material such as various alumina, chromia, zircon, zirconia, fireclay, etc. The particle size of the fine powder raw material is not limited as long as it is a particle size generally recognized as a fine powder raw material in this field, but is preferably less than 0.1 mm, more preferably less than 0.08 mm. If the particle size of the fine powder raw material is less than 0.1 mm, it is preferable because it is easy to ensure the bonding force between the particles.

[0029] The content of the fine powder raw material in the entire refractory raw material is preferably 5.0% by mass or more, more preferably 8.0% by mass or more. When the content of the fine powder raw material is 5.0% by mass or more, it is preferable because it is easy to ensure the bonding force between particles. In addition, the content of the fine powder raw material in the entire refractory raw material is preferably 45% by mass or less, more preferably 40% by mass or less. When the content of the fine powder raw material is 45% by mass or less, it is preferable because it is easy to ensure the breathability.

[0030] The glaze (frit) can promote neck growth of the aggregate raw material. The type of glaze is not particularly limited, and may be any known glaze such as various silicate glasses, borosilicate glasses, zircon-based glasses, and phosphate glasses. The content of the glaze in the entire refractory raw material is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, based on the aggregate raw material and the fine powder raw material. If the content of the glaze is 0.2% by mass or more, it is preferable because it is easy to ensure the bonding force between particles. In addition, the content of the glaze in the entire refractory raw material is preferably 10% by mass or less, more preferably 8.0% by mass or less, based on the aggregate raw material and the fine powder raw material. If the content of the glaze is 10% by mass or less, it is preferable because it is easy to ensure the breathability.

[0031] 2. Other Ingredients The porous refractory may also contain other components, such as residues from the burnout of binders, residues from the burnout of raw materials, etc.

[0032] (Air permeability characteristics of porous refractories) 1.Average pore size The average pore diameter of the porous refractory is 230 μm or less, preferably 225 μm or less, more preferably 220 μm or less, and further preferably 215 μm or less. When the average pore diameter is 230 μm or less, penetration of molten steel is easily suppressed.

[0033] Here, the average pore size of the porous refractory is the cumulative 50% pore size based on the volume of pores, as specified by JIS R1655 "Method for testing pore size distribution of molded fine ceramics by mercury intrusion porosimetry" (hereinafter referred to as mercury intrusion porosimetry). Hereinafter, the symbol for the average pore size is referred to as d50.

[0034] 2. Pore size distribution The span value a, which represents the pore size distribution of the porous refractory, is 0.8 or less, preferably 0.7 or less, more preferably 0.6 or less, and further preferably 0.55 or less. When the span value a is 0.8 or less, it is possible to prevent the presence of excessively large pores on the premise that the average pore size is constant, and it is easy to suppress the penetration of molten steel.

[0035] Here, the span value a is expressed by equation (1). a = (d10-d90) / d50 (1) In formula (1), d50 is the average pore diameter described above, and d10 and d90 are the cumulative 10% pore diameter and cumulative 90% pore diameter, respectively, from the larger pore diameter side on a pore volume basis determined by the mercury intrusion method of JIS R1655.

[0036] 3.Porosity The porosity of the porous refractory is preferably 40% or less, more preferably 38.5% or less, and further preferably 37% or less. A porosity of 40% or less contributes to suppressing the penetration of molten steel and is preferable for ensuring the strength of the porous refractory.

[0037] Here, the porosity of the porous refractory is specified according to JIS R2205 "Method of measuring apparent porosity, water absorption rate and specific gravity of refractory bricks".

[0038] 4.Ventilation rate The permeability of porous refractories is 1.2(×10 -10 m 2 ) or more, preferably 1.5(×10 -10 m 2 ) or more, more preferably 1.7(×10 -10 m2 ) or more, and more preferably 1.9 (× 10 -10 m 2 ) or more. The ventilation rate is 1.2 (×10 -10 m 2 ) or more, the gas can be easily blown in efficiently.

[0039] Here, the air permeability of the porous refractory material is specified by JIS R2115 "Test method for air permeability of refractories".

[0040] [Method for producing porous refractory material] The porous refractory material according to this embodiment is manufactured by a method including a kneading step of kneading the refractory raw material with an acrylic resin having an outer percentage of 3% by mass or more and 15% by mass or less relative to 100% by mass of the refractory raw material to obtain a kneaded mixture, a molding step of molding the kneaded mixture to obtain a molded body, and a firing step of firing the molded body to obtain a porous refractory material.

[0041] (Kneading process) In the kneading step, the refractory raw material and the acrylic resin are kneaded together. In addition, as optional components, a binder and other components may also be kneaded together. After the kneading step is completed, a kneaded mixture containing particulate acrylic resin is obtained.

[0042] 1.Refractory raw materials The refractory raw material is as described above.

[0043] 2. Acrylic resin Acrylic resin is used as the burnt-off raw material. The acrylic resin is typically a polymer of an acrylic acid ester or a polymer of a methacrylic acid ester. The acrylic resin may be, for example, a known polymethylmethacrylate, polyethylmethacrylate, polymethylacrylate, polyethylacrylate, etc. The acrylic resin may be a copolymer or a crosslinked polymer. Various acrylic resins can be used in the present invention, but polymethylmethacrylate (PMMA) is preferably used.

[0044] The average particle size of the acrylic resin is 30 μm or more, preferably 35 μm or more, more preferably 40 μm or more, even more preferably 45 μm or more, and most preferably 50 μm. When the average particle size of the acrylic resin is 30 μm or more, the breathability of the porous refractory material is easily ensured.

[0045] The average particle size of the acrylic resin is 70 μm or less, preferably 65 μm or less, more preferably 60 μm or less, and even more preferably 55 μm or less. When the average particle size of the acrylic resin is 70 μm or less, the pore size and porosity of the porous refractory material are suppressed, so that the penetration of molten steel is easily suppressed and strength is easily ensured.

[0046] Here, the average particle size of the acrylic resin is the cumulative 50% diameter of the volume-based particle size distribution specified by JIS Z8825 "Particle size analysis - Laser diffraction and scattering method." Hereinafter, the symbol for the average particle size is referred to as D50.

[0047] The span value A, which represents the particle size distribution of the acrylic resin, is 3.5 or less, preferably 3.0 or less, more preferably 2.5 or less, and further preferably 2.0 or less. When the span value A is 3.5 or less, the pore size distribution of the resulting porous refractory material is easily narrowed.

[0048] Here, the span value A is expressed by equation (2). A = (D90-D10) / D50 (2) In formula (2), D50 is the aforementioned average particle size, and D10 and D90 are the particle sizes at which the cumulative volume is 10% by volume and 90% by volume, respectively, from the smaller particle size, in the cumulative distribution of particle sizes specified by JIS Z8825 "Particle size analysis - Laser diffraction and scattering method."

[0049] The D50, D10 and D90 of the acrylic resin can be measured using a laser diffraction particle size distribution measuring device.

[0050] An acrylic resin having a predetermined particle size and / or a predetermined particle size distribution can be produced by known techniques and is also available as a commercial product.

[0051] The amount of the acrylic resin added is 3% by mass or more, preferably 4.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 6.0% by mass or more, based on 100% by mass of the refractory raw material. When the amount of the acrylic resin added is 3% by mass or more, based on 100% by mass of the refractory raw material, the breathability of the porous refractory material is easily ensured.

[0052] The amount of the acrylic resin added is 15% by mass or less, preferably 14% by mass or less, more preferably 13% by mass or less, and further preferably 12% by mass or less, based on 100% by mass of the refractory raw material. When the amount of the acrylic resin added is 15% by mass or less, based on 100% by mass of the refractory raw material, the pore size and porosity of the porous refractory material are suppressed, the penetration of molten steel is easily inhibited, and strength is easily ensured.

[0053] 3. Binder In addition to the refractory raw material and the acrylic resin, a binder may be kneaded as desired. As the binder, a known organic binder or inorganic binder may be used. As the organic binder, dextrin, lignin sulfonate, polyvinyl alcohol, molasses, phenolic resin, etc. may be exemplified, and as the inorganic binder, sodium silicate, aluminum phosphate, etc. may be exemplified. It is preferable that the binder does not leave a residue after firing. In order to prevent the particle shape of the acrylic resin in the kneaded mixture from being damaged, it is preferable that the binder is, for example, a component that does not dissolve the acrylic resin, or is added in an amount that does not substantially dissolve the acrylic resin.

[0054] The amount of binder added is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and even more preferably 0.8% by mass or more, based on 100% by mass of the refractory raw material. When the amount of binder added is 0.2% by mass or more, various raw materials are easily kneaded uniformly, which is preferable. In addition, the amount of binder added is preferably 10% by mass or less, more preferably 8.0% by mass or less, and even more preferably 5.0% by mass or less. When the amount of binder added is 10% by mass or less, it is preferable because it is possible to prevent shape changes caused by volatilization or burning of the binder.

[0055] 4.Other ingredients In addition to the refractory raw material, acrylic resin, and binder, other components may also be kneaded. For example, hexamine, which is a hardener for phenolic resin, may be used. In order to prevent the particle shape of the acrylic resin in the kneaded mixture from being damaged, it is preferable that the other components are components that do not dissolve the acrylic resin, or are added in an amount that does not substantially dissolve the acrylic resin.

[0056] The kneading step can be carried out by a known kneading device. A known device is, for example, a Conner mixer. Kneading may be started after all the raw materials such as the refractory raw material and the acrylic resin are put into the mixer, or the raw materials may be put into the mixer in a predetermined order while the kneading is proceeding. The output of the mixer and the kneading time can be adjusted by those skilled in the art.

[0057] (molding process) In the molding step, the kneaded mixture obtained in the kneading step is transferred to a desired mold and press molded. For example, a known friction press can be used as the apparatus for press molding. The maximum pressure of the press molding is preferably 10 MPa or more, more preferably 20 MPa or more. If the pressure of the press molding is 10 MPa or more, it is preferable from the viewpoint of uniform porosity inside the molded body. In addition, the maximum pressure of the press molding is preferably 300 MPa or less, more preferably 250 MPa or less. If the pressure of the press molding is 300 MPa or less, it is preferable from the viewpoint of ensuring the air permeability of the porous refractory material, since excessive deformation of the burnt raw material can be avoided.

[0058] The undried molded body obtained after the press molding is preferably dried thereafter. By drying the molded body, the binder solvent and other volatile solvents are volatilized, and the occurrence of cracks in the next firing step can be suppressed. The drying temperature is preferably 50°C or higher, more preferably 80°C or higher. A drying temperature of 50°C or higher is preferable from the viewpoint of removing volatile components contained in the molded body. In addition, the drying temperature is preferably 300°C or lower, more preferably 200°C or lower. A drying temperature of 300°C or lower is preferable from the viewpoint of ensuring breathability, since excessive deformation of the burnt raw material can be avoided. The drying time is preferably 5.0 hours or more, more preferably 10 hours or more. A drying time of 5.0 hours or more is preferable from the viewpoint of removing volatile components contained in the molded body. In addition, the drying time is preferably 80 hours or less, more preferably 50 hours or less. A drying time of 80 hours or less is preferable from the viewpoint of ensuring breathability, since excessive deformation of the burnt raw material can be avoided.

[0059] When the above molding process is completed, a molded body containing particulate acrylic resin is obtained.

[0060] (Firing process) In the firing step, the molded body obtained in the molding step is fired to obtain a porous refractory. In the firing step, the particulate acrylic resin, which is the raw material to be burned, is burned and pores are formed in the porous refractory. As an apparatus for firing the molded body into a porous refractory, for example, a known industrial kiln can be mentioned.

[0061] The firing temperature in the firing step is preferably 1000° C. or higher, more preferably 1200° C. or higher. A firing temperature of 1000° C. or higher is preferable from the viewpoint of burning off the burnt raw materials without leaving any residue and improving the air permeability. The upper limit of the firing temperature is not particularly limited, but may be, for example, 2000° C.

[0062] The firing time in the firing step is preferably 10 hours or more, more preferably 20 hours or more. A firing time of 10 hours or more is preferable from the viewpoint of burning off the burnt raw material without leaving any residue and improving the air permeability. The upper limit of the firing time is not particularly limited, but may be, for example, 200 hours.

[0063] [How to use porous refractories] The porous refractory material can be used, for example, in the manufacture of gas blowing plugs. The porous refractory material can also be used in electric furnaces, ladles, AOD furnaces, tundishes, etc. EXAMPLES

[0064] [Measurement of physical properties of burned raw materials] Three kinds of burnt raw materials, acrylic resin (PMMA), wood chips and polystyrene resin, were subjected to particle size measurement, crushing test and heat resistance test.

[0065] The average particle diameter D50 and the span value A of the particle diameter were measured using a laser diffraction particle size distribution measuring device (Partica LA-960 manufactured by Horiba, Ltd.).

[0066] The crushing test was carried out using a metal spacer. Specifically, 2 g of the burnt raw material was placed between two metal flat plates, and the two metal flat plates were pressed together using a vice for 5 minutes. An optical microscope was used to examine the state of the burnt raw material before and after pressure application. If there was no deformation of the particles before and after pressure application, the crushing resistance was rated as "good," and if there was deformation of the particles, the crushing resistance was rated as "poor."

[0067] The heat resistance test was carried out using a hot air circulation dryer. Specifically, 10 g of the burnt raw material was weighed out, placed in a metal container, and heated at 200°C in an air atmosphere for 6 hours, after which it was cooled to room temperature. An optical microscope was used to examine the condition of the burnt raw material before and after heating. If there was no deformation of the particles before and after heating, the heat resistance was rated as "good", and if there was deformation of the particles, the heat resistance was rated as "poor".

[0068] Table 1: Measurement results of physical properties of burned raw materials [Table 1]

[0069] As shown in Table 1, the D50 of the acrylic resin, wood chips and polystyrene resin was all 50 μm. From the span value A, it was found that the particle size distribution of the acrylic resin was sharper than that of the naturally derived wood chips.

[0070] In the crushing test, the acrylic resin did not deform before and after the pressure was applied, and had good crushing resistance. On the other hand, the wood chips deformed before and after the pressure was applied, and had poor crushing resistance.

[0071] In the heat resistance test, the acrylic particles maintained their shape and had good heat resistance, whereas the polystyrene resin completely melted when heated and had poor heat resistance.

[0072] From the above results, it was found that acrylic resin has good both crush resistance and heat resistance. It was found that acrylic resin is suitable as a burn-off raw material for the purpose of not losing its shape during the molding process and forming the desired pores during the baking process.

[0073] [Production of porous refractories] (Kneading process) The refractory raw material, the burnt raw material, the binder and the water were mixed in a Conner mixer to obtain a mixed mixture.

[0074] The aggregate raw materials in the refractory raw materials were 74% by weight of spherical alumina (alumina 99.5%) with a particle size of 1.0-0.5 mm, and 12% of mullite (alumina 60%, silica 33%) with a particle size of 1.7-0.3 mm. The fine powder raw materials in the refractory raw materials were 3% by weight of fine alumina (alumina 99.5%) with a particle size of 45 μm or less, 2% by weight of chromium oxide (average particle size 2 μm, chromia 99.5%), 5% by weight of zircon (particle size 45 μm or less, zirconia 66%, silica 33%), and 4% by weight of fireclay (particle size 75 μm or less, silica 49%, alumina 34%).

[0075] The various burnt raw materials were mixed in the mixing ratio described below, with respect to 100% by mass of the refractory raw material.

[0076] The binder, magnesium lignosulfonate solution (a 50 wt % aqueous solution of magnesium lignosulfonate), was mixed in an amount of 2 mass % on an outer basis with respect to 100 mass % of the refractory raw material.

[0077] As an auxiliary, water was blended in an amount of 1.5% by mass on an outer basis based on 100% by mass of the refractory raw material.

[0078] (molding process) The kneaded mixture was pressed using a friction press at a maximum pressure of 98 MPa, and then dried at 120° C. for 12 hours.

[0079] (Firing process) The molded body was fired at 1720°C for 120 hours in an industrial kiln to obtain a porous refractory material.

[0080] [Evaluation of Porous Refractories] The permeability of the porous refractory was measured according to JIS R2115 "Test method for permeability of refractories". Measurements were performed using cylindrical test pieces with a diameter of about 50 mm and a length of about 50 mm. Nitrogen was used as the measurement gas.

[0081] The porosity of the porous refractory material was measured according to JIS R2205 "Method of measuring apparent porosity, water absorption and specific gravity of firebricks" by cutting the porous refractory material into a cylindrical shape with a diameter of approximately 50 mm and a length of approximately 50 mm, and using water as the liquid medium to measure the porosity.

[0082] The average pore diameter d50 and the span value a, which indicates the pore diameter distribution, of the porous refractory were measured by the mercury intrusion method of JIS R1655. Measurements were performed using spherical test pieces with a diameter of approximately 15 mm. The pore diameter was measured by the mercury intrusion method under the conditions of a contact angle of 130° and a surface tension of 0.485 N / m.

[0083] In the present invention, from the viewpoint of providing a porous refractory having good air permeability and capable of easily suppressing the penetration of molten steel, the porous refractories were comprehensively evaluated into the following three levels of "A," "B," and "C" in the order of high air permeability, small porosity, pore diameter, and smallest variation in pore diameter. "A" Ventilation rate is 1.9 (x10 -10 m 2 ) or more, the porosity is 37% or less, the average pore diameter is 215 μm or less, and the span value a is 0.55 or less. "B" Breathability is 1.2 (x10 -10 m 2 ) or more, the porosity is 40% or less, the average pore diameter is 230 μm or less, and the span value a is 0.8 or less, which does not satisfy the requirement of "A." "C" Does not meet the requirements of "B".

[0084] 1. Different types of burnt materials In Example 1, a porous refractory was manufactured using acrylic resin (D50=50μm, span value A=1.80) as the burnt raw material. As a comparative example, a porous refractory was manufactured without using the burnt raw material, or using wood chips (D50=50μm, span value A=2.90) or polystyrene resin (D50=50μm, span value A=1.80). The amount of each burnt raw material added was 9wt% relative to 100% by mass of the refractory raw material. The air permeability characteristics of the manufactured porous refractories are shown in Table 2.

[0085] Table 2: Air permeability characteristics of different burnt materials [Table 2]

[0086] As shown in Table 2, in Example 1, in which acrylic resin was used as the burnt raw material, high air permeability was obtained and the overall evaluation was "A." On the other hand, in Comparative Example 1, in which no burnt raw material was used, the air permeability was low and the overall evaluation was "C." This is thought to be because a porous refractory material containing many interconnected air pores was obtained by burning off the acrylic resin.

[0087] Moreover, Example 1, which used acrylic resin, had high air permeability and was given an overall rating of "A," whereas Comparative Examples 2 and 3, which used other burnt raw materials (wood chips or polystyrene resin), had insufficient air permeability and were given an overall rating of "C." This is thought to be because acrylic resin can maintain its shape during the molding process and is burnt away without leaving any residue during the baking process, whereas the other burnt raw materials lose their shape during the molding process or are left unburned during the baking process.

[0088] 2. Amount of acrylic resin added Porous refractories were manufactured by changing the amount of acrylic resin added using acrylic resin (D50=50μm, span value A=1.80). The air permeability properties of the manufactured porous refractories are shown in Table 3.

[0089] Table 3: Air permeability characteristics when the amount of acrylic resin added is changed [Table 3]

[0090] As shown in Table 3, when the amount of acrylic resin added was between 3 and 15 wt%, a porous refractory material with good performance was obtained with an overall evaluation of "A" or "B". On the other hand, in Comparative Example 4, where the amount added was low, the air permeability was insufficient. In Comparative Example 5, where the amount added was high, the porosity and average pore diameter d50 were high. Therefore, it is considered that the strength and resistance to molten steel penetration in Comparative Example 5 are insufficient.

[0091] 3. About acrylic resin D50 The amount of acrylic resin added was set to 9wt%, and the average particle diameter D50 of the acrylic resin was changed to produce a porous refractory. The span value A of the acrylic resin was 1.80 in all cases. The air permeability properties of the produced porous refractories are shown in Table 4.

[0092] Table 4: Air permeability characteristics when D50 of acrylic resin is changed [Table 4]

[0093] As shown in Table 4, when the D50 of the acrylic resin was between 30 μm and 70 μm, a porous refractory with good performance was obtained. On the other hand, in Comparative Example 6, where the D50 was small, the air permeability was insufficient. In Comparative Example 7, where the D50 was high, the average pore diameter d50 was high. Therefore, it is considered that the resistance to molten steel penetration in Comparative Example 7 was insufficient.

[0094] 4. Span value A of acrylic resin The amount of acrylic resin added was set to 9 wt%, the average particle diameter D50 of the acrylic resin was set to 50 μm, and the span value A of the particle diameter of the acrylic resin was changed to manufacture a porous refractory. The air permeability properties of the manufactured porous refractory are shown in Table 5.

[0095] Table 5: Air permeability characteristics when span value A of acrylic resin is changed [Table 5]

[0096] As shown in Table 5, when the span value A of the acrylic resin was 3.5 or less, a porous refractory with good performance was obtained with an overall evaluation of "A" or "B." On the other hand, in Comparative Example 8, in which the span value A of the acrylic resin was large, the span value a of the pore size was high. Therefore, it is considered that the resistance to molten steel penetration in Comparative Example 8 is insufficient. [Industrial Applicability]

[0097] The present invention can be used, for example, in gas blowing plugs.

Claims

1. The average pore diameter d50, which is the cumulative 50% pore diameter on a volume basis of the pores specified by the mercury intrusion method according to JIS R1655, is 230 μm or less, the pore diameter span value a expressed by the formula (1) is 0.8 or less, and the air permeability specified by JIS R2115 is 1.2 (×10 -10 m 2 ) or higher. a=(d10-d90) / d50 (1) d50 is the average pore diameter, and d10 and d90 are the cumulative 10% pore diameter and cumulative 90% pore diameter from the larger pore diameter side, based on the volume of pores specified by the mercury intrusion method, respectively.

2. The porous refractory according to claim 1, having a porosity specified by JIS R2205 of 40% or less.

3. A kneading step of kneading the refractory raw material with an acrylic resin in an amount of 3% by mass or more and 15% by mass or less relative to 100% by mass of the refractory raw material to obtain a kneaded mixture; A molding step of molding the kneaded mixture to obtain a molded body; and A firing step of firing the molded body to obtain a porous refractory material, The acrylic resin has an average particle diameter D50, which is a cumulative 50% diameter of a volume-based particle size distribution specified by a laser diffraction / scattering method of JIS Z8825, of 30 μm or more and 70 μm or less, and a span value A of the particle diameter expressed by formula (2) is 3.5 or less. A=(D90-D10) / D50 (2) D50 is the average particle diameter, and D10 and D90 are the cumulative 10% diameter and cumulative 90% diameter, respectively, from the smaller particle diameter side of the volume-based particle size distribution determined by the laser diffraction / scattering method.

4. The method according to claim 3 , wherein the molding process includes a press molding step, and a maximum pressure of the press molding step is 10 MPa or more.

5. 4. The method according to claim 3, wherein the refractory raw material comprises 55% by weight to 95% by weight of aggregate raw material having a particle size of 0.1 mm to 5.0 mm, and 5.0% by weight to 45% by weight of fine powder raw material having a particle size of less than 0.1 mm.

6. A gas-blowing plug comprising the porous refractory material according to claim 1 or 2.

Citation Information

Patent Citations

  • Porous refractory material

    JP2007217260A

  • Air-permeability refractory and its manufacturing method

    JP2012062232A

  • Method for producing porous refractory material and porous refractory material

    JP2013001584A

  • Porous refractory

    JP2014043377A

  • Porous ceramic compositions, filters, and articles

    JP2019505365A